2003
DOI: 10.1177/1538192702250620
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Role of Social Capital in Access to College for Latinas: Toward a College Opportunity Framework

Abstract: Using life history research methods, this study sought to understand how relationships with family and school personnel affect postsecondary opportunities for Latina students. The focus is on primary and secondary school experiences of two groups of Latina students and how those experiences influenced their opportunities to pursue postsecondary education. Findings suggest exposure to or accumulation of high or low volumes of social capital or institutional neglect and abuse limits or expands students’ perceive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
188
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 179 publications
(191 citation statements)
references
References 17 publications
(31 reference statements)
3
188
0
Order By: Relevance
“…In general, Latino high school students are less likely than others to receive encouragement from school personnel to pursue four-year higher education (Gonzalez, Stoner, & Jovel, 2003;. They are also less likely to enroll in advanced math (Bozick & Lauff, 2007;Gandara & Contreras, 2009;.…”
Section: Discussionmentioning
confidence: 99%
“…In general, Latino high school students are less likely than others to receive encouragement from school personnel to pursue four-year higher education (Gonzalez, Stoner, & Jovel, 2003;. They are also less likely to enroll in advanced math (Bozick & Lauff, 2007;Gandara & Contreras, 2009;.…”
Section: Discussionmentioning
confidence: 99%
“…Their underrepresentation in colleges and universities has been influenced not by a lack of academic ability (K. P. Gonzalez, Stone, & Jovel, 2003) but by the rising costs of college, increased standards in admissions criteria, and inadequate secondary education preparation (Auerbach, 2004;Valenzuela, 1999). This struggle is no different for Latino 1 students.…”
mentioning
confidence: 99%
“…Indeed, students from different SES backgrounds differ substantially in financial support received (or not) from their families, which directly influences their higher education outcomes (Swartz, 2008). SES is a composition of education level, occupation, and income (Baker, 2014), and research has shown that family social capital, which is closely related to parents' education and occupation, influences students' access to college (Gonzá lez, Stoner, & Jovel, 2003). It is necessary to ask whether parents' education level influences student borrowing beyond the impact of family income.…”
Section: Family Ses and Student Borrowingmentioning
confidence: 99%